Looking Back: Folklore Studies in Tamil Nadu - Shanmugavel, K. (Faculty of Arts University of Jaffna, Sri Lanka, 2022)
Though the Postgraduate and Research Department of Folklore at St. Xavier’s College, Palayamkottai, Tamil Nadu, was established in 1987, Folklore Studies as a discipline had already been initiated two decades earlier. Since then, it has flourished as a key discipline within the institution. One of the pioneering scholars of Folklore Studies, Na. Vanamamalai (hereafter, Na. Va.) was not only based in Palayamkottai but also situated his research forum, Nellai Aivukkuzhu (Nellai Research Group) in this location. Na. Va. organized monthly meetings initiating debates on various themes cutting across disciplines such as History, Literature, Sociology, Anthropology and Folklore and published the essays presented at those meetings in a journal, popularly known as Aaraichi. When the Jesuit management, which administers St. Xavier’s College (SXC), Palayamkottai, decided to start an academic programme on Folklore, riding on Prof. S. D. Lourdu’s expertise on Folklore, the research atmosphere created by Na. Va. played a crucial role in establishing the discipline of Folklore as an interdisciplinary one. Both the Department of Folklore and its sisterly institute, Folklore Resources & Research Centre, have contributed to create debates in Folklore and Culture Studies through field-based research, documentation and publication. However, commercialization of education and its consequences pushed disciplines like Folklore to the margins. This paper documents major developments in the Folklore discipline at Palayamkottai. It attempts to situate Folklore Studies in Palayamkottai, first by focusing on the role of eminent folklorist Na. Vanamamalai and the Department of Folklore, SXC. In the subsequent sections, the paper analyses the major contributions by the Department and the kind of crisis it has been facing during the past few years. The final sections deal with how the Department attempts to negotiate with the reality and tries to establish its identity taking into consideration the contemporary educational context. It also briefly discusses some practices that the Department can adopt to recover itself from the present crisis.
Keywords: Folklore; Nattar; Vazhakkarukal; Na. Vanamamalai; S.D. Lourdu; Subaltern